The Effectiveness of the RADEC Learning Model in Strengthening Religious Character and Critical Thinking among Elementary School Students - Nana Suryana; Wahyu Sopandi; Yadi Ruyadi (Postgraduate, University of Mataram, 2026)
This research is based on the persistently low critical thinking skills of students and the suboptimal internalization of religious character values in the learning process in elementary schools. Learning that is still oriented toward memorization and teacher-centered approaches results in students being less engaged in reflective, dialogical, and contextual activities. However, the demands of 21st-century education and the Pancasila Student Profile emphasize the importance of strengthening religious character and critical reasoning skills in an integrated manner starting from elementary school. This study aims to analyze the effectiveness of the RADEC learning model in strengthening religious character and critical thinking skills in elementary school students. This study used a quantitative approach with a one-group pretest-posttest design. The subjects were 125 elementary school students in Cluster IV, Pagerageung District, Tasikmalaya Regency. The RADEC learning model was implemented in the learning process using the syntax